The decline and fall of Europe - Bongiovanni, Francesco M. (2012)
Moving from the birth of Europe to the current crisis, this irreverent and topical book questions the relevance of the European Union today, addressing issues ranging from immigration and Turkish integration to the sovereign debt crisis, and whether this will prove to be merely the beginning of intractable economic challenges.